A comparison of attitudes around collaboration held by traditional healers and professional nurses in the Western Cape - Tyhala, Brenda (Department of Psychiatry and Mental Health, 2025)
Background Many mental health care system users consult traditional healers while also seeking biomedical forms of healing. Despite this, there is no formalized working relationship between these two systems, which operate in parallel and independently. The government has taken considerable steps towards facilitating collaboration; however, this has not yielded the desired outcome, because of educational gaps, lack of appreciation, recognition, mutual respect, and mistrust between the two systems. Building a trusting relationship and learning from each other should be prioritized. Aim This study aimed to survey the attitudes of Xhosa-speaking professional nurses and Xhosa-speaking traditional healers, on the treatment of mentally ill people, to assess whether their respective professions could cooperate with regards to the diagnosis and treatment of mentally ill individuals, and to determine the feasibility of future collaboration towards comprehensive mental health care services. Method Thirty Xhosa-speaking professional nurses and 30 Xhosa-speaking traditional healers completed a structured questionnaire. The questionnaire covered practice details, attitudes, perception of the other profession, diagnosis and management of mental illness. Results There was recognition of the one profession by the other and willingness to collaborate for the benefit of the patient by both, professional nurses and traditional healers. There is still an element of mistrust, gaps in knowledge and a superiority complex from both systems. Conclusion There is room for collaboration between traditional healers and biomedical practitioners. Efforts to afford opportunities for both systems to interact and learn from each other need to be supported and prioritized by the government and both professions.